The New Trainee Effect in Tracheal Intubation Procedural Safety Across PICUs in North America: A Report From National Emergency Airway Registry for Children*. Issue 12 (December 2020) - Branca, Aline; Tellez, David; Berkenbosch, John; Rehder, Kyle J.; Giuliano, John S.; Gradidge, Eleanor; Shults, Justine; Turner, David A.; Nett, Sholeen; Krawiec, Conrad; Edwards, Lauren R.; Pinto, Matthew; et al.
Abstract : Objectives: Tracheal intubation carries a high risk of adverse events. The current literature is unclear regarding the "New Trainee Effect" on tracheal intubation safety in the PICU. We evaluated the effect of the timing of the PICU fellow academic cycle on tracheal intubation associated events. We hypothesize 1) PICUs with pediatric critical care medicine fellowship programs have more adverse tracheal intubation associated events during the first quarter (July–September) of the academic year compared with the rest of the year and 2) tracheal intubation associated event rates and first attempt success performed by pediatric critical care medicine fellows improve through the 3-year clinical fellowship. Design: Retrospective cohort study. Setting: Thirty-seven North American PICUs participating in National Emergency Airway Registry for Children. Patients: All patients who underwent tracheal intubations in the PICU from July 2013 to June 2017. Interventions: None. Measurements and Main Results: The occurrence of any tracheal intubation associated events during the first quarter of the academic year (July–September) was compared with the rest in four different types of PICUs: PICUs with fellows and residents, PICUs with fellows only, PICUs with residents only, and PICUs without trainees. For the second hypothesis, tracheal intubations by critical care medicine fellows were categorized by training level and quarter for 3 years of fellowship (i.e., July–September of 1st yr pediatric critical care medicine fellowship = first quarter, October–December of 1st yr pediatric critical care medicine fellowship = second quarter, and April–June during 3rd year = 12th quarter). A total of 9, 774 tracheal intubations were reported. Seven-thousand forty-seven tracheal intubations (72%) were from PICUs with fellows and residents, 525 (5%) with fellows only, 1, 201 (12%) with residents only, and 1, 001 (10%) with no trainees. There was no difference in the occurrence of tracheal intubation associated events in the first quarter versus the rest of the year (all PICUs: July–September 14.9% vs October–June 15.2%; p = 0.76). There was no difference between these two periods in each type of PICUs (all p ≥ 0.19). For tracheal intubations by critical care medicine fellows ( n = 3, 836), tracheal intubation associated events significantly decreased over the fellowship: second quarter odds ratio 0.64 (95% CI, 0.45–0.91), third quarter odds ratio 0.58 (95% CI, 0.42–0.82), and 12th quarter odds ratio 0.40 (95% CI, 0.24–0.67) using the first quarter as reference after adjusting for patient and device characteristics. First attempt success significantly improved during fellowship: second quarter odds ratio 1.39 (95% CI, 1.04–1.85), third quarter odds ratio 1.59 (95% CI, 1.20–2.09), and 12th quarter odds ratio 2.11 (95% CI, 1.42–3.14). Conclusions: The New Trainee Effect in tracheal intubation safety outcomes was not observed in various types of PICUs. There was a significant improvement in pediatric critical care medicine fellows' first attempt success and a significant decline in tracheal intubation associated event rates, indicating substantial skills acquisition throughout pediatric critical care medicine fellowship. Abstract : Supplemental Digital Content is available in the text.